2011
DOI: 10.1007/s00192-011-1422-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of long-term outcome between Manchester Fothergill and vaginal hysterectomy as treatment for uterine descent

Abstract: The MF procedure is equally effective to the VH and should be considered as a surgical option that allows preservation of the uterus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 15 publications
3
23
1
Order By: Relevance
“…There was no difference in patient-reported symptom relief and satisfaction 1 year after surgery, but the rate of severe complications was significantly lower in the cervical amputation group. The findings corroborate those of previous studies comparing these two techniques [8, 13, 14]. In the subgroup of patients where no concomitant anterior colporrhaphy was performed, the cervical amputation group had a significantly lower symptomatic recurrence rate 1 year after surgery than the vaginal hysterectomy group, indicating that cervical amputation may be superior to vaginal hysterectomy in the treatment of apical descent.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There was no difference in patient-reported symptom relief and satisfaction 1 year after surgery, but the rate of severe complications was significantly lower in the cervical amputation group. The findings corroborate those of previous studies comparing these two techniques [8, 13, 14]. In the subgroup of patients where no concomitant anterior colporrhaphy was performed, the cervical amputation group had a significantly lower symptomatic recurrence rate 1 year after surgery than the vaginal hysterectomy group, indicating that cervical amputation may be superior to vaginal hysterectomy in the treatment of apical descent.…”
Section: Discussionsupporting
confidence: 88%
“…In some papers cervical amputation is even described as an obsolete procedure [12]. However, based on the current literature, procedures including amputation of the cervix appear to be equally as effective with regard to anatomical cure and recurrence rates, but with less morbidity than vaginal hysterectomy [8, 1315]. …”
Section: Introductionmentioning
confidence: 99%
“…Personal interviews can be an alternative to questionnaires where women with possible complications can relate to their sexual functioning and receive medical advice or be referred to other professionals. Thys et al [16] suggested recently that the emotional, cultural and personal wishes of the women are need to be considered as part of the medical decision for the type of the surgery. The preservation of the uterus, is considered by many women as important to their female identity [13].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, up until now, the typical conservative uterovaginal prolapse surgery is hysterectomy, in spite of common complications such as excessive blood loss, long post operational recovery, middle compartment recurrence, and impairment of bladder function [12,[14][15][16]. One recent research study showed signiWcantly less blood loss and shorter operation time in the Manchester procedure group but higher rate of incomplete emptying of the bladder compared to the vaginal hysterectomy group [16].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation